Validation of the "perceptions regarding pRE-symptomatic Alzheimer’s disease screening” (PRE-ADS) questionnaire in the German population: attitudes, motivations, and barriers to pre-symptomatic dementia screening - Angelidou, Ioanna A.; Stocker, Hannah; Beyreuther, Konrad; Teichmann, Birgit (Journal of Alzheimer's disease, 2024)
Background: Attitudes, motivations, and barriers to pre-symptomatic screening for Alzheimer’s disease (AD) in the general population are unclear, and validated measurement tools are lacking. Objective: Translation and validation of the German version